Computational comparative genomics in cyanobacteria - Mantas, Maria José Q. (The University of Edinburgh, 2023)
Cyanobacteria are an ancient clade of photosynthetic prokaryotes, varying in morphology, physiology, biochemistry and habitat. They evolve by typical prokaryotic mechanisms including horizontal gene transfer (HGT). Some species produce toxins (cyanotoxins) that present health hazards to humans and animals, with potential harm to local economies. The biosynthetic pathways and roles of some cyanotoxins are unclear. The rapid increase in high quality publicly available genomes presents opportunities for discovery from comparative genomics in cyanobacteria. The work presented here focuses on three topics in cyanobacteria, using bioinformatics analyses of 130 cyanobacterial genomes. Firstly, I consider hypotheses for the biosynthesis and physiology of the non-encoded neurotoxin 2,4-diaminobutanoic acid (2,4-DAB). Secondly, I consider hypotheses for the biosynthesis and potential roles of its structural analogue, β-N-methylaminoalanine (BMAA). These topics use similar methodology: pairwise and multiple sequence alignment, profile hidden Markov models, substrate specificity and active site identification, and the reconstruction of gene phylogenies. We show that some species have genes involved in known biochemical pathways to 2,4-DAB – genes coding for proteins in the aspartate 4-phosphate pathway (including the diaminobutanoate-2-oxo-glutarate transaminase, the downstream decarboxylase, diaminobutanoate decarboxylase, and ectoine synthase) – and BMAA (homologs of the Staphylococcus aureus genes sbnA and sbnB). We highlight the possible involvement of 2,4-DAB and BMAA in the production of siderophores. We show that the biosynthesis of 2,4-DAB and BMAA is likely to be confined to a limited number of species, or to occur via different, unknown, pathways. Thirdly, I investigate hypotheses concerning the association of HGT events with environmental context. I test existing hypotheses claiming that genetic exchanges are more frequent in extreme habitats (versus mesophilic) and in terrestrial habitats (versus aquatic). My results, based on reconciliation of gene trees with the species tree, do not suggest a link between the prevalence of HGT and extreme or terrestrial environments. I highlight the need for complete descriptions of the isolation source and culture type (axenic, non-axenic monocyanobacterial culture, environmental sample), the need for accurate and robust methods for HGT inference, and for more objective and detailed criteria for environmental classification and of cyanobacterial species. This work contributes to research into cyanobacterial neurotoxins and provides insights into the prevalence and distribution of HGT in cyanobacteria.
Keywords: Cyanobacteria; Cyanobacteria; 2,4-Diaminobutanoic acid; 2,4-Diaminobutyric acid; 2,4-DAB; Diaminobutanoate-2-oxo-glutarate transaminase; Diaminobutanoate decarboxylase; Siderophores; Ectoine; 3-N-Methyl-2,3-diaminopropanoic acid; BMAA; 2,3-Diaminopropanoic acid; 2,3-DAP; Paenilamicins; Biochemical Pathways; Horizontal Gene Transfer; Lateral Gene Transfer; HGT; Comparative Genomics; Phylogenetics; Environment; Bioinformatics; Genomes